Psychometric Validation of the Dutch Version of the Promotive and Prohibitive Voice Scale - Sijbom, Roy B. L.; Koen, Jessie (Frontiers in Psychology, 2021)
The aim of this three-study report was to validate the Dutch version of the promotive and prohibitive voice scale, developed by Liang, Farh, and Farh (2012), and to further embed the constructs of promotive and prohibitive voice within their nomological network. Promotive voice refers to the expression of suggestions for improving work practices, whereas prohibitive voice refers to the expression of concerns about practices and behaviors that are detrimental. In Study 1 (N = 121), confirmatory factor analyses (CFAs) provided evidence for the two-factor structure, which was replicated in the other two studies. In Study 2 (NT1 = 209/NT2 = 107), we investigated the convergent and discriminant validity of the promotive and prohibitive voice scale, and tested measurement invariance across gender and time. Results provided validity evidence, partial scalar invariance for gender, and scalar invariance across time. In Study 3 (N = 149), we expanded the nomological network of the promotive and prohibitive voice scales through their relationship with personal initiative, approach temperament, and risk propensity. Taken together, our results provide strong evidence for the validity of the Dutch version of the promotive and prohibitive voice scale.